Latent classes and predictors of aggression trajectories in Korean adolescents: Implications for targeted prevention - Eunha Jeong (PLoS ONE, 2026)
School violence and juvenile crime are emerging social problems in Korea. Adolescent aggression, an important mediator linking risk factors in the developmental environment to more serious deviant behavior, exerts long-term cumulative effects into adulthood. Thus, a longitudinal examination of aggression among adolescents is crucial. This study identified differential longitudinal trajectories of aggression in Korean adolescents and investigated the predictors distinguishing these latent classes. Data were used from 2,016 adolescents from Waves 1–5 (2018–2022) of the Korean Children and Youth Panel Survey. The overall trajectory of adolescent aggression was explored using latent growth curve modeling, and latent class growth modeling was conducted to identify possible heterogeneity in aggression trajectories. Multinomial logistic regression was used to analyze the predictors of each latent class. Latent growth curve modeling revealed an overall decline in aggression across adolescents. Latent class growth modeling identified three latent classes—moderate-decreasing, low-increasing, and high-decreasing—indicating heterogeneous developmental patterns of adolescent aggression. Key predictors of latent class included gender, perceived economic status, impulsivity, depression, smartphone dependency, negative parenting attitude, and negative peer relationships. Adolescent aggression follows heterogeneous developmental pathways shaped by individual, family, and school factors. These findings highlight the importance of identifying distinct aggression trajectory groups and their key predictors and demonstrate the value of a trajectory-based approach to guide targeted prevention strategies.